Potato production with quality seed and improved technology in Assam - Somani, Ashok K; Borthakur, Devajit; Mahant, Sanjay; Thomas, George (Indian Horticulture, 2022)
Assam is among the top 10 potato producing states of India but yields are very low as compared to national average due to several constraints. Utkal Tubers India Private Limited, Bengaluru conducted a trial in a farmer’s field in Assam with its seed and technology during 2020- 21. Average yields of two varieties (Kufri Pukhraj and Kufri Jyoti) was 11.62t/acre (28.70t/ha) and that of farmer’s local variety and traditional method, it was 3.8 t/acre (9.39 t/ha). In UTIPL’s case, yield is 3 times more than farmer’s own case and higher than national average with further scope to increase it to about 4 times of farmer’s yield. The study shows that there is tremendous scope for improving the yields in Assam.